Minimally invasive plate osteosynthesis with locking compression plate in patients with Vancouver type B1 periprosthetic femoral fractures. Issue 7 (July 2018) - Min, Byung-Woo; Cho, Chul-Hyun; Son, Eun-Suck; Lee, Kyung-Jae; Lee, Si-Wook; Min, Kyung-Keun
Abstract: Background: Periprosthetic femoral fractures (PFF) following total hip arthroplasty (THA) remain one of the most challenging complications to address. Although the principal treatment modalities for Vancouver type B1 fractures are open reduction and internal fixation (ORIF), surgeons have not yet reached a consensus on the optimal method for reduction and fixation. We therefore investigated whether minimally invasive plate osteosynthesis (MIPO) using locking compression plate (LCP) would lead to favorable outcomes for patients with Vancouver type B1 PFFs. In addition, we also compared the outcomes of patients treated with MIPO to those treated with ORIF. Method: We retrospectively evaluated the clinical and radiographic outcomes of a series of 21 Vancouver type B1 PFFs treated with MIPO and LCP between February 2011 and February 2017. The mean duration of follow-up was 33.8 months. We also compared outcomes of these patients to those of patients with 19 Vancouver type B1 fractures treated with ORIF between April 2006 and December 2011. Results: Fracture healing without complications was achieved in 20 (95.2%) out of 21 cases in the MIPO group and in 14 (87.5%) out of 16 cases in the ORIF group. There was one case of fixation failure with stem subsidence in the MIPO group. In the ORIF group, there were 2 nonunion with metal failure. Operation time was significantly shorter and intraoperative blood loss was significantly less in the MIPO group compared to the ORIF group. However, there were no significant differences in frequency of transfusion, time-to-union, walking abilities, modified Harris hip score, or complications. Conclusion: The radiological and clinical outcomes of MIPO using LCP in patients with Vancouver type B1 PFFs were shown not to be inferior to ORIF and resulted in fewer intraoperative complications than ORIF. If care is taken regarding the stability of femoral implant and optimal surgical techniques, MIPO may be a recommended option in the treatment of Vancouver type B1 periprosthetic fracture.